2014
DOI: 10.1038/bjc.2014.608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endoscopy screening on stage at gastric cancer diagnosis: results of the National Cancer Screening Programme in Korea

Abstract: Background:Although gastric cancer screening is common among countries with a high prevalence of gastric cancer, there is little data to support the effectiveness of this screening. This study was designed to determine the differences in stage at diagnosis of gastric cancer according to the screening history and screening method (upper gastrointestinal series (UGIS) vs endoscopy).Methods:The study population was derived from the National Cancer Screening Programme (NCSP), a nationwide organised screening progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 15 publications
(15 reference statements)
4
77
0
2
Order By: Relevance
“…These measures can be broadly classified into two groups: those that aim to detect gastric cancer itself (cancer screening), and those that aim to evaluate the premalignant condition of gastric mucosa (risk stratification) [2]. Double-contrast upper gastrointestinal barium X-ray radiography (UGI-XR) [3][4][5] and upper gastrointestinal endoscopy (UGI-ES) [6][7][8] are the typical measures belonging to the former group, whereas serum markers including anti-Helicobacter pylori (H. pylori) IgG, pepsinogens, gastrin-17, methylation status of several genes, etc. [9][10][11][12][13][14] are representative measures affiliated with the latter group.…”
Section: Introductionmentioning
confidence: 99%
“…These measures can be broadly classified into two groups: those that aim to detect gastric cancer itself (cancer screening), and those that aim to evaluate the premalignant condition of gastric mucosa (risk stratification) [2]. Double-contrast upper gastrointestinal barium X-ray radiography (UGI-XR) [3][4][5] and upper gastrointestinal endoscopy (UGI-ES) [6][7][8] are the typical measures belonging to the former group, whereas serum markers including anti-Helicobacter pylori (H. pylori) IgG, pepsinogens, gastrin-17, methylation status of several genes, etc. [9][10][11][12][13][14] are representative measures affiliated with the latter group.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have shown reductions in stomach cancer mortality in screened populations, the target group, onset, and modality of screening programs remain controversial. 37,[42][43][44][45][46] Prevention and treatment of carcinogenic infections that lead to these observed cancer patterns in low SDI countries have the potential to decrease future cancer burden as well as reducing associated diseases like cirrhosis in endemic areas. 47 In addition, limiting transmission can lead to prevention efforts that are sustained beyond 1 generation.…”
mentioning
confidence: 99%
“…In Korea, since a nationwide gastric cancer screening program was started in 1999 as part of the National Cancer Screening Program, persons 40 years or older have been undergoing biennial upper endoscopies or upper gastrointestinal series. 2 Owing to mass screening programs and recent improvements in diagnostic technique, early detection in a resectable state followed by treatment of gastric cancer has increased and, therefore, the overall survival rates have increased. 2 Until now, in patients <40 years, routine gastric cancer screening is not recommended.…”
Section: Introductionmentioning
confidence: 99%
“…2 Owing to mass screening programs and recent improvements in diagnostic technique, early detection in a resectable state followed by treatment of gastric cancer has increased and, therefore, the overall survival rates have increased. 2 Until now, in patients <40 years, routine gastric cancer screening is not recommended. Gastric cancer is predominantly diagnosed in older patients.…”
Section: Introductionmentioning
confidence: 99%